2004
DOI: 10.3928/1081-597x-20040903-21
|View full text |Cite
|
Sign up to set email alerts
|

Smoothness of Ablation on Polymethylmethacrylate Plates With Four Scanning Excimer Lasers

Abstract: PURPOSE: To perform a quantitative evaluation of smoothness of ablation on polymethylmethacrylate (PMMA) using four scanning excimer lasers available commercially for photorefractive surgery. METHODS: Ablations were done on PMMA plates with dimensions 100 x 50 x 1 mm. Four scanning excimer lasers were used, two with flying spot technology (Zeiss-Meditec MEL-70, and a Russian-made unit, Microscan) and two Nidek models with scanning slit delivery systems and an expanding iris diaphragm (EC-5000 and EC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Plastic models have been used in refractive surgery research and calibration for a long time, especially for the assessment of roughness and calibration of pulse energy (radiant exposure or fluence) [1,2,5,25,26]. However, it has not been until recently that plastic models have been used to study in detail the changes in the shape of the flat or spherical surfaces, after refractive surgery [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plastic models have been used in refractive surgery research and calibration for a long time, especially for the assessment of roughness and calibration of pulse energy (radiant exposure or fluence) [1,2,5,25,26]. However, it has not been until recently that plastic models have been used to study in detail the changes in the shape of the flat or spherical surfaces, after refractive surgery [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that the laser with Scanning spot technology produced smooth ablations even up to −9.00 D. Ablation smoothness is also influenced by spot positioning algorithms. Dago et al performed ablations on PMMA plates using four scanning excimer lasers, two with flying spot technology (Zeiss-Meditec MEL-70, and a Russian-made unit, Microscan) and two Nidek models with scanning slit delivery systems and an expanding iris diaphragm (EC-5000 and EC-5000 CX) [2]. The smoothest surface was obtained in samples produced by Zeiss-Meditec MEL-70 unit (RMS = 112 ± 23 nm), followed by the Nidek EC-5000 CX (RMS = 153 ± 12 nm), and the Microscan (RMS = 181 ± 11 nm).…”
Section: Introductionmentioning
confidence: 99%
“…The other important one is the analysis of optical results of artificial treatments on specific polymer plates. PMMA plates are widely used to test the ablation depth and to guarantee the refractive results of the excimer laser equipment from the first step of the design to the user-side daily calibration procedure [ 8 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Laser systems often utilize plastic material ablations for calibration [ 14 ] and optimization of system parameters [ 16 ]. The use of Polymethylmethacrylate (PMMA) as a calibration material has been well analyzed in the past, and used to develop comprehensive models, considering applied correction, as well as laser beam characteristics and ablative spot properties [ 17 , 18 , 19 , 20 , 21 ]. However, PMMA ablation may also be affected by the variations in temperature and humidity [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%